The Cajal body and the nucleolus: "In a relationship" or "It's complicated"?. Issue 6 (3rd June 2017) - Trinkle-Mulcahy, Laura; Sleeman, Judith E.
ABSTRACT: From their initial identification as 'nucleolar accessory bodies' more than a century ago, the relationship between Cajal bodies and nucleoli has been a subject of interest and controversy. In this review, we seek to place recent developments in the understanding of the physical and functional relationships between the 2 structures in the context of historical observations. Biophysical models of nuclear body formation, the molecular nature of CB/nucleolus interactions and the increasing list of joint roles for CBs and nucleoli, predominantly in assembling ribonucleoprotein (RNP) complexes, are discussed.